Parametric Optimization of Friction Stir Welding of Al-Mg-Si Alloy: A Case Study - Khan, Nasir; Rathee, Sandeep; Srivastava, Manu (Yugoslav Journal of Operations Research, 2021)
Al-Mg-Si alloys have wide applications in industries such as aerospace, marine, automobile, construction, and so on. In this work, newly developed friction stir welding (FSW) was utilized for the joining of AA6082-T6 alloy.The  effect of major FSW process variables like rotational speed, traverse speed, and shoulder diameter of the tool is studied over microstructural and mechanical characteristics of friction stir welded (FSWed) joints. Experimental design was done using Taguchi method (L9 orthogonal array). Three factors viz. rotational speed, welding speed, and diameter of the tool shoulder were taken at three levels each. Mathematical modelling was developed in order to optimize the tensile strength of weld joints. Analysis of variance (ANOVA) was utilized to determine the percentage contribution of input variables. The results of the present study exhibit that shoulder diameter, rotation, and welding speed of the tool affect significantly the mechanical strength of FSWed joints.